Molecular Mechanisms Underpinning the Circulation and Cellular Uptake of Mycobacterium ulcerans Toxin Mycolactone - Tello Rubio, Bruno; Bugault, Florence; Baudon, Blandine; Raynal, Bertrand; Brûlé, Sébastien; Morel, Jean-David; Saint-Auret, Sarah; Blanchard, Nicolas; Demangel, Caroline; Guenin-Macé, Laure (Frontiers in Pharmacology, 2021)
Mycolactone is a diffusible lipid toxin produced by Mycobacterium ulcerans, the causative agent of Buruli ulcer disease. Although bacterially derived mycolactone has been shown to traffic from cutaneous foci of infection to the bloodstream, the mechanisms underpinning its access to systemic circulation and import by host cells remain largely unknown. Using biophysical and cell-based approaches, we demonstrate that mycolactone specific association to serum albumin and lipoproteins is necessary for its solubilization and is a major mechanism to regulate its bioavailability. We also demonstrate that Scavenger Receptor (SR)-B1 contributes to the cellular uptake of mycolactone. Overall, we suggest a new mechanism of transport and cell entry, challenging the dogma that the toxin enters host cells via passive diffusion.